2017
DOI: 10.1080/02770903.2017.1281296
|View full text |Cite
|
Sign up to set email alerts
|

Parents' asthma information needs and preferences for school-based asthma support

Abstract: This research clearly describes a need for school-based asthma support, including asthma-related policies, procedures and education on asthma and first aid in Saudi primary schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“… 12–15 18 19 24 The costs and difficulties in obtaining days off-work for caregivers were also mentioned in this study by both HCPs and caregivers, and this issue has been raised frequently in previous studies. 10 13–15 17 20 21 26 Caregivers’ beliefs, a mistrust in hospitals and doctors, combined with advice from non-HCPs, caused many to prefer the use of natural remedies over prescribed drugs. This was also the case for ethnic minority caregivers in the UK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12–15 18 19 24 The costs and difficulties in obtaining days off-work for caregivers were also mentioned in this study by both HCPs and caregivers, and this issue has been raised frequently in previous studies. 10 13–15 17 20 21 26 Caregivers’ beliefs, a mistrust in hospitals and doctors, combined with advice from non-HCPs, caused many to prefer the use of natural remedies over prescribed drugs. This was also the case for ethnic minority caregivers in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…7 These phases have been used in a systematic review to classify reported barriers and facilitators to healthcare access for any disease, 8 and could be applied also to asthma healthcare. Several studies have investigated barriers and facilitators to health and home care access for children with asthma from the caregivers' perspective, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] but only a few from the perspective of healthcare professionals' (HCPs). 26 27 Most such studies have been done in the USA and Europe.…”
Section: Key Messagesmentioning
confidence: 99%
“…20,21,25 In studies of the experiences of families, the families having child with asthma, emphasized the lack of training and psychological support provided by healthcare professionals. 19,[33][34][35] Moreover, in previous studies, it was reported that families had problems with school personnel concerning managing asthma and that many families did not send their children to school during periods of exacerbations. 36 The mothers are generally the primary caregivers of children, and many mothers feel alone in managing asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative evaluations of community-based programs for children with asthma are limited (6). Some qualitative literature sought general feedback from parents/caregivers, healthcare providers and community stakeholders about caring for children with asthma (7)(8)(9)(10), but no qualitative evaluations were identified that have obtained feedback and suggestions from parents and family members who participated in an asthma home-visiting program.…”
Section: The Community Asthma Initiative Has a Quality Improvement Mo...mentioning
confidence: 99%